2020
DOI: 10.1021/acsanm.0c03216
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Palladium Atoms Dispersed on Silicoaluminophosphate-31 (SAPO-31) for the Semihydrogenation of Alkynes

Abstract: Supported single-atom catalysts have become one of the most exciting frontiers in heterogeneous catalysis. The physicochemical properties of these materials are highly interesting; however, the generation of stable single atoms on solid supports is still challenging. Herein, we report an efficient and operationally simple postsynthesis method, consisting of spatial confining, freeze-drying, and reducing steps, for the construction of singly dispersed palladium atoms on SAPO-31 (Pd 1 /SAPO-31) with promising ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The dispersion of Pd atoms in Pd 1 / h-BN was measured to be nearly 98% (SI Table S4), suggesting the vast majority of Pd is atomically dispersed. 14,46,47 An electron paramagnetic resonance (EPR) measurement was employed to detect any unpaired electrons in the samples (Figure 3f). Compared with defective h-BN and Pd NPs/h-BN, a distinct signal was noticed at a g value of 2.003, suggesting the presence of unpaired electrons in Pd 1 /h-BN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dispersion of Pd atoms in Pd 1 / h-BN was measured to be nearly 98% (SI Table S4), suggesting the vast majority of Pd is atomically dispersed. 14,46,47 An electron paramagnetic resonance (EPR) measurement was employed to detect any unpaired electrons in the samples (Figure 3f). Compared with defective h-BN and Pd NPs/h-BN, a distinct signal was noticed at a g value of 2.003, suggesting the presence of unpaired electrons in Pd 1 /h-BN.…”
Section: Resultsmentioning
confidence: 99%
“…The N 1s spectrum showed three types of nitrogen (Figure S10d): N–B–O at 398.1 eV, N–B (NB 3 ) at 398.5 eV, and N–Pd at 398.7 eV, respectively. ,, For Pd 3d spectrum (Figure e), the Pd 5/2 peak of Pd 1 /h-BN at 336.5 eV corresponds to the positively charged palladium atoms, in line with the XAFS results. The dispersion of Pd atoms in Pd 1 /h-BN was measured to be nearly 98% (SI Table S4), suggesting the vast majority of Pd is atomically dispersed. ,, An electron paramagnetic resonance (EPR) measurement was employed to detect any unpaired electrons in the samples (Figure f). Compared with defective h-BN and Pd NPs/h-BN, a distinct signal was noticed at a g value of 2.003, suggesting the presence of unpaired electrons in Pd 1 /h-BN.…”
Section: Resultsmentioning
confidence: 99%
“…Pd is regarded as the most Pt-like metal and is widely used to catalyze hydrogenation and C–C bond formation. 37 Pd based SACs were synthesized and proved efficient in many processes of industrial significance, such as selective hydrogenation of unsaturated hydrocarbons, 38–42 ketone, aldehydes and nitriles, 43–46 Suzuki coupling, 47 hydrochlorination and dechlorination, 48,49 electrocatalysis 50 and CO oxidation, 51,52 etc. Recently, it was also shown that adsorption and reactions of NO may drive bulk Pd or commercial Pd black to dispersion into zeolite channels as cationic Pd reaction centers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, electrochemical potential window strategy is proposed to be effective in producing high-loading and high-purity SACs, such as Pt 1 /N-graphene, Pd 1 /N-graphene, Ni 1 /N-graphene, Pt 1 /Fe 3 O 4 , Pd 1 /Fe 3 O 4 and Ni 1 /Fe 3 O 4 ; 171 Spatial sites separation strategy could be used to fabricate carbon-supported atomically isolated Ni catalyst, which is highly active in electrochemical CO 2 reduction reaction; 172 Post-synthesis method, including spatial confining, freeze-drying and reducing steps, has been verified efficient for the construction of Pd 1 /silicoaluminophosphate-31 (Pd 1 /SAPO-31) catalyst. 173 …”
Section: Synthesis Approaches Of Sacsmentioning
confidence: 99%